Ogan Komering Ilir: Primadona's PDA in South Sumatera: Ogan Komering Ilir : PDA Primadona Sumatera Selatan - Asiati, Diah Isnaini; Usman, Hamid; Abdullah, Mismiwati (Journal of Islamic and Muhammadiyah Studies, 2024)
The Regional Leadership of Ogan Komering Ilir Regency (PDA OKI) is one of the PDAs in South Sumatra Province which is considered slow to develop. It is therefore necessary to carry out a study as a tabayyun effort by regional leaders. This research is a qualitative descriptive study based on a case study which attempts to summarize a phenomenon to the reality. The research object is the PDA OKI in the key person-based. The main data collection method is interviews with triangulation analysis techniques. The results of the research show that the quiet activity of the PDA OKI is because even though regional expansion has occurred, the vastness of the OKI territory is still in sense, so it has an impact on feedback, tools and facilities, as well as development opportunities. Furthermore, the results of the analysis show that the PDA OKI is not an area that is silent in its activities, in fact it has the opportunity to grow better and become a primadona because of the potential of its cadres and opportunities for communication development.Highlights: Regional Challenges: The vast OKI area limits development and feedback opportunities for PDA OKI. Potential for Growth: PDA OKI has untapped potential due to its capable cadres and leaders. Positive Outlook: Despite challenges, PDA OKI holds promise to become a regional primadona. Keywords: Feedback, Tools and Facilities, Opportunities, Potential Cadres, Communication Development